2020
DOI: 10.2298/zipi2002418s
|View full text |Cite
|
Sign up to set email alerts
|

Modern learning approaches in higher education: A review of the literature

Abstract: This paper provides a review of the literature on the evaluation of two learning approaches in higher education: problem-based learning (PBL) and student-centred learning (SCL). We were interested in dissemination of these learning approaches in higher education in both developing and developed countries. We identified 47 experimental and quasi-experimental studies published before March 2020, from medical, engineering and other fields of higher education. Historically PBL has been mostly app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…The reason is that mainly fundamental/theoretical subjects and specialties are useful in a plan-oriented approach but are not in a market-oriented economy. To the best of our knowledge, few articles have addressed this topic [4]. An ageing academic staff, a non-competitive culture, and the unattractiveness of being employed in higher education for younger generations, among others, explain this reluctance to change.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reason is that mainly fundamental/theoretical subjects and specialties are useful in a plan-oriented approach but are not in a market-oriented economy. To the best of our knowledge, few articles have addressed this topic [4]. An ageing academic staff, a non-competitive culture, and the unattractiveness of being employed in higher education for younger generations, among others, explain this reluctance to change.…”
Section: Discussionmentioning
confidence: 99%
“…In general, PBL supports students to obtain academic knowledge through real life cases. At the same time, it introduces them to research, on how to use and understand research findings, but also on how to understand and use data [4].…”
Section: Introductionmentioning
confidence: 99%
“…All the reasons mentioned above contribute to difficulties in the implementation of more modern teaching methods, as novel methods typically require a willingness to change and adapt, as well as specific training, which are not generally part of the culture of education [10]. Thus, the research team analyzed the literature to find modern learning approaches to suggest solutions for solving these issues [11]. The previous literature has shown that one of the modern approaches that can be applied in successfully reforming higher education from a more theoretical to a more practical model is PBL [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%